Chronic lymphocytic leukemia developing in a case of chronic myelogenous leukemia - accelerated phase: A rare case with review of the literature - Narender Kumar; Jasmina Ahluwalia; Pankaj Malhotra; Man Updesh Singh Sachdeva (Wolters Kluwer Medknow Publications, 2013)
Chronic myelogenous leukemia (CML) and chronic lymphocytic leukemia (CLL) are two different and common hematological neoplasms. Their coexistence is rare, especially CLL developing in a patient of CML. Till date, only a few cases are reported and all had chronic myeloid leukemia - chronic phase earlier. We report the first case of CLL developing in a patient initially diagnosed in an accelerated phase of chronic myeloid leukemia. The clonality of both CML and CLL was proven by cytogenetic, molecular and flow cytometric studies.